Knowledge of Syntax Versus Reading Skill in ESP - Aryusmar, Aryusmar (Humaniora, 2010)
Article clarified the relationship between knowledge of syntax and reading skill in English for specific purposes. The research was conducted at the Industrial Engineering Faculty of Trisakti University in 2002 with sample of 100 students using simple random sampling by Lottery. Data was analyzed by using simple regression test and simple correlation test. The result of the research revealed that there was a positive relationship between knowledge of syntax and reading skill in English for specific purposes. It is concluded that reading skill in English for specific purposes can be improved by increasing knowledge of syntax.